Fluorescent lactose-derived catanionic aggregates: synthesis, characterisation and potential use as antibacterial agents. Issue 28 (29th February 2016) - Bettoschi, Alexandre; Brisson, Alain; Caltagirone, Claudia; Falchi, Angela M.; Isaia, Francesco; Lippolis, Vito; Loi, Giovanni; Loi, Monica; Murgia, Sergio; Pilia, Roberta; Serra, Corrado; Tan, Sisareuth
Abstract : The antibacterial properties of catanionic surfactants based on fluorescent lactose-derivative organic salts using low-cost starting materials were investigated towards multi-drug-resistant Gram-positive bacteria. Abstract : The spread of infections from multi-resistant bacteria in hospitals around the world is raising at an alarming rate. With the increasing capacity of bacteria to develop resistance to traditional antibiotics that target a particular metabolic pathway inside the cell, the use of nanoparticles as therapeutic agents is gaining importance because of their ability to attack bacterial membranes without evoking resistance. We have synthesized the catanionic surfactantsCoum12–Coum18, based on fluorescent lactose-derivative organic salts using low-cost starting materials. In water, they self-assemble spontaneously to form stable aggregates at a physiological pH. The antibacterial properties ofCoum12–Coum18 were investigated towards multi-drug-resistant Gram-positive bacteria ( Staphylococcus aureus and Enterococcus faecalis ) and Gram-negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ). CompoundCoum18 was found to have both a bacteriostatic and a bactericidal activity towards Gram-positive bacteria, although the values of both the MIC and MBC (32 μg mL −1 ) suggest only a topical use of the molecule. The valuable results that were found provide a challenging task for further investigation aimed at the development of this class of antibacterial drugs. In vitro fluorescence microscopy gave insight into the interaction between the aggregates and the cellular membranes on HeLa and CHO cells.